Performativity and deviation: creative and pedagogical processes in performing arts (Revista Educação, Artes e Inclusão, 2022)
This work integrates a research on deviation strategies in contemporary theater. The objective of the study is, through the analysis of works and processes, to reflect on dramaturgical and scenic composition procedures that devia-te from traditional poetics. This paper particularly discusses experiences developed in the Theatrical Direction Laboratory: Theater, Rite and Performance, componente of the Bachelor of Theatrical Direction of the Federal University of Bahia School of Theater. The purpose of the component is that, with the guidance of the teacher-researcher, the student-artists develop an experience of theatrical direction with hybrid scenic processes that transits in diverse artistic territories. The component's basic bibliography covers topics such as Antonin Artaud and the Theater of Cruelty; Jerzy Grotowski and Teatro Pobre; Renato Cohen and the Language of Performance in Brazil. The theoretical-methodological perspective is based on the notions of performativity and theatricality which, in turn, transit between different fields of knowledge such as anthropology, linguistics and sociology.
Keywords: theater; performance; deviation